2014
DOI: 10.1080/09297049.2014.986082
|View full text |Cite
|
Sign up to set email alerts
|

Event rate and reaction time performance in ADHD: Testing predictions from the state regulation deficit hypothesis using an ex-Gaussian model

Abstract: According to the state regulation deficit (SRD) account, ADHD is associated with a problem using effort to maintain an optimal activation state under demanding task settings such as very fast or very slow event rates. This leads to a prediction of disrupted performance at event rate extremes reflected in higher Gaussian response variability that is a putative marker of activation during motor preparation. In the current study, we tested this hypothesis using ex-Gaussian modeling, which distinguishes Gaussian f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 27 publications
7
27
0
2
Order By: Relevance
“…Similarly, there was greater RTV in ADHD compared to controls, under high demand (very fast or very slow event rates), compared to low demand (medium event rates) conditions (Metin et al, 2016) reflecting deficient behavioural adaptation of task performance to changing task demands. Deficient context regulation of neural (EEG) activity in ADHD is also seen in the transition from rest to task conditions (Rommel et al, 2016; Skirrow et al, 2015); a finding that was reversed in response to methylphenidate (Skirrow et al, 2015).…”
Section: A Comparative Analysis Of Adhd and Mind Wanderingmentioning
confidence: 99%
“…Similarly, there was greater RTV in ADHD compared to controls, under high demand (very fast or very slow event rates), compared to low demand (medium event rates) conditions (Metin et al, 2016) reflecting deficient behavioural adaptation of task performance to changing task demands. Deficient context regulation of neural (EEG) activity in ADHD is also seen in the transition from rest to task conditions (Rommel et al, 2016; Skirrow et al, 2015); a finding that was reversed in response to methylphenidate (Skirrow et al, 2015).…”
Section: A Comparative Analysis Of Adhd and Mind Wanderingmentioning
confidence: 99%
“…More specifically, under slow event rates in particular, participants with ADHD showed slower reaction times than controls, while under fast event rates, they showed elevated rates of errors of commission. A study by the same group found evidence of an accentuated inverted-U relationship across four levels of event rate on reaction time variability in ADHD (Metin et al, 2016): ADHD was associated with greater variability at both very long and very short rates. This variation as a function of event rate has been explained in terms of a deficit in the application of effort in situations with a suboptimal energetic state (e.g., Wiersema et al, 2006a; Sonuga-Barke et al, 2010; Metin et al, 2012, 2016; Johnstone and Galletta, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…With a prevalence rate of 5% in children and 1 to 7% in adults ( Polanczyk and Rohde, 2007 ; Polanczyk et al, 2007 ) Attention-Deficit/Hyperactivity Disorder (ADHD) is a common developmental disorder characterized by impaired levels of attention and/or hyperactive-impulsive behaviors. Apart from behavioral symptoms, subjects show various deficits in executive functions, response inhibition ( Boonstra et al, 2005 ; Willcutt et al, 2005 ), and motivational functions ( Metin et al, 2012 , 2014 ).…”
Section: Introductionmentioning
confidence: 99%